2020
DOI: 10.5430/ijhe.v9n3p248
|View full text |Cite
|
Sign up to set email alerts
|

Praxis for Accelerated Improvement in Research (PAIR)

Abstract: This article introduces the Praxis for Accelerated Improvement in Research (PAIR) as a transformative research management paradigm drawn from the participatory action research program focused on research production and publication in a private higher education institution in Manila, Philippines. PAIR mentoring scheme upholds establishing a committed and caring relationship between the mentor and the mentee, thereby developing a shared vision towards research. PAIR mentoring further underscores the need to inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
(21 reference statements)
1
1
0
Order By: Relevance
“…The institution recorded very few publications in Scopus-indexed journals. The results are parallel with Anito, Limjap, and Padagas [30], which revealed that their HEI-respondent registered only three Scopus 133 papers within a 10-year period (2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017). This implies that while the institution consciously endeavors to generate several studies, very few of these papers are published in refereed journals, including those indexed in Scopus.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The institution recorded very few publications in Scopus-indexed journals. The results are parallel with Anito, Limjap, and Padagas [30], which revealed that their HEI-respondent registered only three Scopus 133 papers within a 10-year period (2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017). This implies that while the institution consciously endeavors to generate several studies, very few of these papers are published in refereed journals, including those indexed in Scopus.…”
Section: Discussionsupporting
confidence: 60%
“…HEIs may also consider subjecting their institutional journals for CHED accreditation and possible indexing to other citation databases such as ACI. While research is etched in government policies on higher education, Philippines HEIs need to introduce innovative research programs that could help accelerate the production and publication of research [30], specifically in Scopus-indexed journals.…”
Section: Discussionmentioning
confidence: 99%